The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.aogh.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Practice, Knowledge, and Barriers for Screening of Hepatocellular Carcinoma Among High-Risk Chinese Patients

Abstract: Health care professionals and community leaders should actively inform patients regarding the benefits of HCC screening through design of educational programs. Such interventions are expected to increase knowledge about HCC and HCC screening, as well as improve screening adherence and earlier diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…An estimated figure has shown that less than 5% of rural patients are able to afford 1 year of treatment as opposed to 40% of patients in more developed regions [29]. In addition to issues concerning accessibility and costs of treatment, Chinese patients in rural regions also have poor health awareness; many infected-individuals are unaware of their HBV infection until symptoms appear [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…An estimated figure has shown that less than 5% of rural patients are able to afford 1 year of treatment as opposed to 40% of patients in more developed regions [29]. In addition to issues concerning accessibility and costs of treatment, Chinese patients in rural regions also have poor health awareness; many infected-individuals are unaware of their HBV infection until symptoms appear [31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…The HCC-related knowledge section was modified from previous studies 18 20 under consultation with six liver disease experts. This section contained 13 statements each with three choices: “aware”, “uncertain”, and “unaware” ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Questions were adapted from earlier validated surveys. 18 , 20 , 21 After pretesting the questionnaire on 20 patients, necessary modifications were made. Finally, 10 items of possible barriers were finalized: financial issue, accuracy of the surveillance, inadequate information on the place to receive tests as part of the surveillance procedure, the necessity of surveillance, appointment difficulties, time commitment, transportation, lack of a specialist, fear of finding cancer, and fear of pain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Currently, the most widely used diagnostic methods for HCC screening include biannual abdominal ultrasound examination and serum alphafetoprotein measurement. 3 In the United States, all focal liver lesions suspected during ultrasound examination are verified using computed tomography and/or magnetic resonance imaging. 4 The application of these methods makes the diagnosis of HCC a lot more accurate, in which the sensitivity of diagnosis is up to 89% and the specificity reaches as high as 99%.…”
Section: Introductionmentioning
confidence: 99%